APLIKASI PENDIDIKAN LINGKUNGAN HIDUP BAGI ANAK TINGKAT SEKOLAH DASAR DALAM MEMBENTUK KEPEDULIAN ANAK TERHADAP LINGKUNGAN - Hidayatus sholihah; Lum’atun Nadzifah (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2018)
Children’s Forest Program is education program for live environmentally through sound involve primary school children in five school at the Pati regency. In order to provide generation who are care about long lasting nature OISCA as Institution on a self supporting community like support material education environment in CFP program than collaboration with primary school in the Pati regency. This research intent on detect implementation and implication Children’s Forest Program at the mitra school OISCA Pati toward enhancement factor children care in the school area with applying for field research as reference to have data and description about OISCA Pati contribute in the made way for young generation to care concerning about conservation live environmentally. With this research extend expectable to new input at all parties which plunge into an activity in the program education environment in a general manner and particularry OISCA Pati as location have been this researched.